Machine Learning–Derived Fractal Features of Shape and Texture of the Left Atrium and Pulmonary Veins From Cardiac Computed Tomography Scans Are Associated With Risk of Recurrence of Atrial Fibrillation Postablation - Firouznia, Marjan; Feeny, Albert K.; LaBarbera, Michael A.; McHale, Meghan; Cantlay, Catherine; Kalfas, Natalie; Schoenhagen, Paul; Saliba, Walid; Tchou, Patrick; Barnard, John; Chung, Mina K.; Madabhushi, Anant (Circulation. Arrhythmia and electrophysiology, 2021)
[Figure: see text].